2022
DOI: 10.1038/s41419-022-04913-7
|View full text |Cite
|
Sign up to set email alerts
|

CircSCAF8 promotes growth and metastasis of prostate cancer through the circSCAF8-miR-140-3p/miR-335-LIF pathway

Abstract: Circular RNAs (circRNAs) have been increasingly linked to cancer progression. However, the detailed biological functions of circRNAs in prostate cancer (PCa) remain unclear. Using high-throughput circRNA sequencing, we previously identified 18 urine extracellular vesicle circRNAs that were increased in patients with PCa compared with those with benign prostatic hyperplasia. Spearman correlation analysis of the expression levels of the 18 circRNAs between the tumor tissue and matched urine extracellular vesicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Previous studies indicated that miR-140 functions as a tumor suppressor by targeting several kinds of genes, including FEN1 ( 60 ), YES1 ( 62 ) and BIRC6 ( 73 ). Downregulation of miR-140 is implicated in the development of PC by regulating cancer stem cell formation, tumor invasion, and angiogenesis ( 73 , 74 ). We used Target Scan database, Pic Tar, miRcode and Starbase databases to identify miR-140 as a potential miRNA targeting OGT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that miR-140 functions as a tumor suppressor by targeting several kinds of genes, including FEN1 ( 60 ), YES1 ( 62 ) and BIRC6 ( 73 ). Downregulation of miR-140 is implicated in the development of PC by regulating cancer stem cell formation, tumor invasion, and angiogenesis ( 73 , 74 ). We used Target Scan database, Pic Tar, miRcode and Starbase databases to identify miR-140 as a potential miRNA targeting OGT.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, miR-140-3p was predicted to interact with RAD51-AS1 and EIF5A2 jointly by ENCORI. The down-regulation and tumor inhibitory effect of miR-140-3p has been confirmed in a broad spectrum of cancers, such as bladder cancer (Yang et al 2022 ), prostate cancer (He et al 2022a , b ), lung cancer (Huang et al 2019 ), breast cancer (Dou et al 2021 ) and gastric cancer (You et al 2023 ). In OvCA, lncRNA AC005224.4-mediated upregulation of SNAI2 elevated cancer cell invasion and migration by sponging miR-140-3p (Xiong et al 2023 ).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, tumorigenic lncRNA on chromosome 1p13 could lead to the downregulation of some tumor suppressors by interacting with TPR in liver cancer (Yuan et al 2022 ). LncRNA KCNQ1 opposite strand/antisense transcript 1 exerted a tumor-promoting function in OvCA by decreasing eukaryotic translation initiation factor 2B (EIF2B5) expression by recruiting DNA methyltransferases into EIF2B5 promoter (He et al 2022a , b ). In colorectal cancer, NOTCH1-associated lncRNA in T cell acute lymphoblastic leukemia 1 strengthened the proliferative and migrating capacities of the tumor cells by sponging microRNA (miR)-574-5p (Ye et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…circRNA positively regulated PCa bone metastasis by inhibiting downstream miRNA through binding interaction (I don’t quite understand the precise meaning of spongification in this context, if you mean sopping up). Major circRNA/miRNA found to date include circMID1/miR-330-3p ( 100 ), circSCAF/miR-140-3p and miR-335 ( 102 ), circ_SLC19A1/miR-497 ( 104 ), hsa_circ_0062019/miR-195-5p ( 105 ), and circSMARCA5/MiR-432 ( 106 ). These circRNA were highly expressed in both PCa and bone metastasis, and functioned to promote bone metastasis through downstream signaling axes ( Figure 5 ).…”
Section: Association Of Circrna With Pca Bone Metastasismentioning
confidence: 99%